Incompatibility of The PPAT Deed Numbering Period with The BPHTB Validation Period at BAPENDA Jakarta - Al Hadid, Andi Pangerang; Adhari, Ade (Law Development Journal, 2024)
Ownership of Rights to a person is proven by ownership of a Land Certificate that can be transferred to another person, one way is by Sale and Purchase between the Land Owner as the seller and the Buyer. In a transfer of such rights there are taxes that must be paid, one of which is the Land and Building Acquisition Tax or abbreviated as BPHTB and after payment, BPHTB Validation will be carried out with a Maximum Period of 30 Working Days based on the Governor's Regulation and requires a PPAT Deed Number for input. Meanwhile, based on Government Regulations, the PPAT Deed Number has a period of 7 working days from the time it is signed and must be registered with the National Land Agency. Therefore, this creates many multi-interpretations because there is no harmony between one regulation and another. The problem taken in this study is how the inconsistency of the PPAT Deed Number Period with BPHTB Validation. The method used is Normative Jurisprudence with Analytical Descriptive Specifications. The research results show that there is a mismatch between the PPAT Deed Number Period and the BPHTB Validation Period, this condition must be addressed by adjusting the Regulation of the Governor of the Special Capital Region of Jakarta Number 34 of 2022 with Government Regulation Number 24 of 1997 which based on the Hierarchy of Legislation is a higher regulation than the Governor's Regulation.